Reciprocating sliding tribology of brake oil treated carbon fiber reinforced ceramic matrix composites - KUMAR P.; SRIVASTAVA V.K. (My University, 2025)
The effect of brake oil on sliding behavior of carbon/carbon (C/C) and carbon/carbon−silicon carbide (C/C−SiC) composites was investigated with the variation of laminate orientation and surface conformity. The partial and low conformity contacts with the normal and parallel orientations of laminates were considered. The normal load was varied from 50 to 90 N in a step of 10 N. The friction and wear behavior was investigated under reciprocating sliding conditions. The results showed that friction coefficient and wear loss of composites with normal orientation of laminates were larger as compared to those of composites with parallel orientation of laminates. C/C composites with normal orientation of laminates yielded the highest value of friction coefficient. Wear loss decreased by a maximum of 78%, and friction coefficient decreased by a maximum of 49% in low conformity contacts as compared to partial conformity contacts. The presence of brake oil reduced the adhesion tendency of compacted wear debris because the formation of friction film was difficult, and thus, friction behavior was affected. The wear debris retention between the contact surfaces due to confined area motion in reciprocating sliding depicted the tribological behavior. © 2019 The Nonferrous Metals Society of China